Management of Sporadic Vestibular Schwannomas in Children-Volumetric Analysis and Clinical Outcome Assessment - Julian Zipfel; Mykola Gorbachuk; Isabel Gugel; Marcos Tatagiba; Martin U. Schuhmann (MDPI AG, 2022)
Vestibular schwannomas (VS) usually manifest between the 5th and 8th decade of life. Most pediatric cases are associated with Neurofibromatosis type 2 and sporadic VS are rare in this age group. Few case series have been published. We report on our institutional series of sporadic VS in children. We included all cases between 2003 and 2021; 28 of 1635 patients harbored a sporadic VS and were younger than 21 years old. A retrospective review of clinical parameters and surgical data as well as outcomes was performed. All procedures were performed via a retrosigmoid approach. Preoperative imaging was assessed, and tumor volumetry was performed. Mean follow-up was 28 months, symptomatology was diverse. Most children and adolescents presented with hearing loss and tinnitus. All cases with multiple preoperative magnetic resonance imaging scans showed volumetric tumor growth between 1 and 18%/month (mean 8.9 ± 5.6%). Cystic tumor morphology and bone erosion was seen in larger tumors. Gross total resection was possible in 78% of patients and no recurrence was observed. All patients with subtotal resection showed tumor regrowth. Sporadic VS in children are rare and present with a high clinical variability. Surgical resection is the primary therapy and is feasible with favorable results comparable to the adult age group.